Studi Lapisan Hasil Hardfacing Dengan Variasi Arus Dan Elektroda AWS A5.13 EFe2/A5.1 E7018 - Ferry Budhi Susetyo; Himawan Hadi Sutrisno; Rizchi Ayu Suryadewi (Jurnal Asiimetrik: Jurnal Ilmiah Rekayasa & Inovasi, 2021)
The current becomes a factor influencing the hardness value In the welding. The higher the welding current would affect the higher the hardness test results. If the current were used is low it will make it difficult to ignite the electric arc. Aims of this study to determine the effect of welding current (90, 110 and 130 A) and buffer layer on hardness, macro and microstructure layers are result from hardfacing using AWS A5.13 EFe2/AWS A.51 E7018 elektrodes. The hardfacing process uses a Shielded Arc Metal Welding (SMAW) welding machine with DC+ polarity. Hardfacing consists of three layers, 1st layer uses AWS A5.13 EFe2 electrode, 2nd layer uses AWS A.51 E7018 electrode, and 3rd layer uses AWS A5.13 EFe2 electrode. The increase in hardness will occur significantly after hardfacing on the base metal. The higher welding current is resulting the higher hardness value. The hardness of the 130 A specimen is higher than 90 A and 110 A specimen. In the 130 A specimen the hardness value was 468.1 VHN, and in the 90 A specimen the hardness value was 358.94 VHN.